Residential fresh water demand in China: A panel data analysis - Lili Jia; Chao Bao (University of Bonn, Center for Development Research (ZEF), 2014)
The surge of Residential Fresh Water Demand (RFWD) has raised great concern for China's water supply and understanding the driving forces of RFWD is critical to maintain a sufficient water supply. Drawing on the panel dataset from 31 Chinese provinces from 2000 to 2011, we estimate the determinants of the increase in RFWD using Ordinary Least Square (OLS) and Fixed Effects (FE) approaches. We argue that FE should be adopted as it can consider the unobserved heterogeneity among regions such as local social norms regarding hygiene habits and water resource use. Our estimation results indicate that the rapid increase in China's RFWD is mainly attributed to the improvement of household income, the aging society and the urbanization. The results imply that the Chinese government should consider the dynamics of socio-economic conditions and urbanization in reforming water and urban development policies, such as enhancing the capability of water supply services, integrating rural-urban development and encouraging water conservations.
Keywords: 330; Water demand; water resources management; urbanization; panel data analysis